Artificial Intelligence in Indonesia’s Alternative Dispute Resolution: From Digital Facilitator to Adjudicator Partner - Tenri Famauri, Andi; Irwanto, Hartono Tasir; Badarulzaman, Muhammad Hafiz; A. Sapiddin, Andi Syahwiah (Fakultas Hukum, Universitas Muhammadiyah Yogyakarta, 2026)
The rapid expansion of Indonesia’s digital economy has intensified high-volume disputes that surpass the capacity of conventional legal infrastructure, highlighting a persistent law lag. Law No. 30 of 1999 limits arbitrators to human legal subjects, while Law No. 19 of 2016 confines Artificial Intelligence (AI) to a passive electronic instrument without adjudicative authority. This study proposes a reconceptualization of AI as an adjudicator partner within Indonesia’s alternative dispute resolution framework. Using a normative juridical method. This research analysis is based on the principles of dignified justice and human-in-the-loop to evaluate the integration of artificial intelligence (AI) into the adjudication process. The results of the study show that Article 12 of Law Number 30 of 1999 affirms the adjudicative function of human arbiters with the capacity for will, moral judgment, and legal responsibility. This means that AI decision-maker. While technological developments demonstrate a shift in the role of AI from digital facilitator to adjudicator partner supporting legal assessment, human involvement remains essential to ensure moral considerations and oversight of potential algorithmic bias and AI hallucinations in the decision-making process.